International Sustainability Self-Regulatory CSR Certification Standards and the Challenges of Embedding Them in the RMG Production Processes in Bangladesh - Md. Ashadujjaman (Universitas Airlangga, 2019)
Since the Rana Plaza tragedy in 2013, the Ready-Made Garment (RMG) industry, the most vital role-playing sector in the Bangladeshi economy, has faced many challenges, including labour unrest, image crisis, and pressure from local and international stakeholders to ensure worker safety. The tragic incident in 2013 prompted many initiatives for rehabilitation, the amendment of labour laws, the agreement on treaties for factory inspection, etc. As a consequence, national and international compliance bodies were set up to ensure a safe working environment in the RMG production sector in Bangladesh, such as The Accord, The Alliance, WRAP, BSCI, FLA, ETI, SAI, Sedex, etc. Furthermore, most advanced factories adopted their sustainability self-regulatory sets of norms to ensure a better working environment. Although these local and international compliance initiatives triggered notable changes in the sector, to the working environment and the worker safety, in particular, a major challenge arose for the producing factories to simultaneously comply with all the codes of conducts of the different compliance bodies. This study will present an overview of the most common practices required by the different codes of conducts in the Bangladeshi RMG sector and demonstrate how the different standardization organizations challenge the overall compliance in the RMG production processes in Bangladesh. An analysis of these challenges will also be given, finally leading to a list of eight key points that need to be solved by the producers to deal with the current problems in the industry.